2017
DOI: 10.7759/cureus.1421
|View full text |Cite
|
Sign up to set email alerts
|

Successful Trial of Octreotide and Ketorolac for the Management of Increased Biliary Drain Output: A Case Report

Abstract: We describe a 69-year-old male patient with the status of obstructive jaundice post percutaneous biliary drainage for prior obstructive jaundice and who presented with a complaint of generalized weakness and increased output from the drainage tube. The patient developed worsening jaundice, which was noted to be obstructive in nature with a marked dilatation of the biliary tree and a distal obstruction of the common bile duct. Subsequently, a percutaneous biliary drain was placed for symptomatic management. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Of them, only three exceeded outputs of more than 2 liters, as in our patient, and needed aggressive fluid therapy [5]. Similar to our case, another report also described a high output from an EBD of 3–4 liters a day complicated by pre-renal AKI which was effectively treated with octreotide and nonsteroidal anti-inflammatory drugs (NSAIDs) [6]. It is unclear from these reports or available evidence what the mechanism or risk factors for a high-output biliary drain are.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Of them, only three exceeded outputs of more than 2 liters, as in our patient, and needed aggressive fluid therapy [5]. Similar to our case, another report also described a high output from an EBD of 3–4 liters a day complicated by pre-renal AKI which was effectively treated with octreotide and nonsteroidal anti-inflammatory drugs (NSAIDs) [6]. It is unclear from these reports or available evidence what the mechanism or risk factors for a high-output biliary drain are.…”
Section: Discussionsupporting
confidence: 70%
“…However, aggressive fluid therapy, renal support with hemodialysis, octreotide, and NSAIDS were suggested to be effective in the management. The basolateral membrane of cholangiocytes contains secretin receptors which cause a cyclic adenosine monophosphate (cAMP)-dependent increase in bile release [6]. Thus, the use of octreotide was justified based on its ability to inhibit secretin-mediated bile release.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers underline overlooked bile cast nephropathy as a potential cause of renal injury in patients with hyperbilirubinemia, which we excluded in our patient. 4,5 Literature on managing the persistent choleresis from the biliary drain is scarce, although octreotide is reportedly helpful (2). PubMed search for "highvolume biliary excretion" or "percutaneous biliary drainage" combined with "octreotide" or "acute kidney injury" retrieves 21 results, where only three of them are related to our case.…”
Section: Discussionmentioning
confidence: 89%
“…Although we found a report on the beneficial effect of ketorolac, we decided to avoid nonsteroidal anti-inflammatory drugs (NSAID) to avoid potential nephrotoxicity. 1,2 The patient's laparotomy wound healed well, and we removed the stitches. On the ninth postoperative day, we performed secondary cholangiography through a Ttube, demonstrating the passage of bile into the duodenum without signs of residual stones or contrast leakage (Figure 3).…”
Section: Case Reportmentioning
confidence: 99%
“…One of the earliest pieces of literature published byTaber et al in 1982 in the review of 120 cases showed 7 of the patients' daily biliary output exceeded average amount and only three exceeded outputs of more than 2 liters, as in our case demanding fluid resuscitation.2 In another case report published by Jayarajah et al mentioned development of high biliary output AKI in case of blocked SEMS and failure of internal catheterization requiring hemodialysis 6. Literature regarding percutaneous biliary procedure Nepal is limited, a study by Thapa A et al showed promising result in its role in palliation highlighting the need of further large scale study 4,7,8,9. …”
mentioning
confidence: 72%